Laminated filter material, filter, filter unit, and method for manufacturing laminated filter material

The laminated filter material addresses the challenges of dust retention and airflow resistance by using a heat-fused short fiber layer and fiber sheet with optimized properties, resulting in improved mechanical stability and filtration performance.

JP2025060073APending Publication Date: 2025-04-10TOYOBO MC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023170576
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing laminated filter materials face challenges in maintaining high dust retention efficiency and low airflow resistance over time, while also ensuring stable pleat processing and mechanical properties.

Method used

A laminated filter material is developed with a short fiber layer containing core sheath short fibers made of polyolefin resin, heat-fused with a fiber sheet, and optimized for bending rebound properties and breathability, with specific weight and oil adhesion requirements.

Benefits of technology

The optimized laminated filter material achieves improved mechanical properties, stable pleat processing, and increased dust retention while maintaining breathability and collection efficiency, leading to high-performance filters with extended usage life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060073000001_ABST
    Figure 2025060073000001_ABST
Patent Text Reader

Abstract

To provide a laminated filter material which optimizes mechanical characteristics, stabilizes pleat workability, and can increase a dust holding amount while maintaining air permeability and collection efficiency of a filter and a filter unit after pleating.SOLUTION: A laminated filter material in which a short fiber layer containing a core-sheath short fiber composed of a polyolefin-based resin and a fiber sheet are laminated has thickness of 0.8 mm or more and 1.5 mm or less, wherein the short fiber layer and the fiber layer are heat-fused to each other, bending repulsion characteristic is 56×10-4 N or more and 103×10-4 N or less, and air permeability is 33 cc / cm2 / sec or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminated filter medium used in a filter and a method for producing the same. [Background technology]

[0002] Laminated filter media, which mainly uses polyolefin resins, are used as filter media for electrostatic filters for air conditioners, air purifiers, office equipment, etc. Filters are sometimes used as pleated filter units by folding the filter media. In this case, it is necessary to keep the air flow resistance of the filter unit low while maintaining a certain dust collection efficiency for a long period of time, so a filter media with excellent shape stability and relatively high rigidity is preferred even after it is made into a unit.

[0003] Laminated filter media is often composed of a short fiber layer made of relatively heavy short fibers to maintain its shape and a fiber sheet with fine fiber diameters, such as melt-blown nonwoven fabric. In particular, polypropylene-based melt-blown nonwoven fabric can be electrically charged by being treated to electrically charge the fibers, which can greatly contribute to improving dust collection efficiency.

[0004] Conventionally, laminated filter media have been obtained by using polyester thermal bond or chemical bond sheets for the short fiber layer and laminating them with fiber sheets such as the melt-blown nonwoven fabric mentioned above via adhesive. However, in order to obtain high adhesive strength, adhesives are required on multiple ends, and the adhesives tend to clog the nonwoven fabric, resulting in increased pressure loss during ventilation and a shorter service life.

[0005] As a result, there are the following types of laminated filter media that do not require adhesives. For example, there is a laminated filter media in which a thin polypropylene melt-blown nonwoven fabric and a fiber web made of thick, heat-fusible core-sheath fibers are laminated and heat-fused (Patent Document 1). There is also a filter media that uses new core-sheath fibers with a reduced amount of oil attached to the short fiber layer to improve electrostatic charging performance (Patent Document 2), and a filter media in which small holes are formed in advance in the support layer and melt-blown nonwoven fabric, and then heat-bonded (Patent Document 3). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 62-83017 [Patent Document 2] JP 2012-239995 A [Patent Document 3] JP 2014-226629 A Summary of the Invention [Problem to be solved by the invention]

[0007] Regarding the laminated filter media, Patent Document 1 does not consider the strength and rigidity after joining, the pleating processability, etc. Also, Patent Documents 2 and 3 consider the pleating processability to some extent, but because the physical strength, particularly the bending resilience, is low, the filter performance after molding into a pleated filter, particularly the dust retention, tends to be low.

[0008] Therefore, in consideration of the above problems, the present invention aims to provide a laminated filter medium and a manufacturing method thereof that optimize the mechanical properties of the laminated filter medium, stabilizes pleating processability, and enables an increase in the dust retention capacity of the filter after pleating. [Means for solving the problem]

[0009] The inventors have conducted extensive research and have come to solve the above problems by providing the following configuration. 1. A laminated filter medium in which a short fiber layer containing core-sheath short fibers made of polyolefin resin and a fiber sheet are laminated, the thickness being 0.8 mm to 1.5 mm, the short fiber layer and the fiber sheet being heat-sealed, and the bending resilience being 56×10 -4 N or more 103×10 -4 N or less and the air permeability is 33cc / cm 2 / sec or more. 2. The basis weight of the short fiber layer is 65 g / m 2 More than 95g / m 2 2. The laminated filter medium according to claim 1, which is as follows: 3. The laminated filter medium according to the above 1 or 2, wherein the short fiber layer has an oil adhesion amount of 0.1% by weight or less and is electrically charged. 4. The laminated filter medium according to any one of 1 to 3 above, wherein the core-sheath staple fibers have a polypropylene resin core and a polyethylene resin sheath, the staple fiber layer contains two types of staple fibers having different finenesses as the core-sheath staple fibers, and the proportion of the staple fibers with a larger fineness in the staple fiber layer is 80% by weight or more. 5. The fiber sheet has a breathability of 36cc / cm 2 5. The laminated filter medium according to any one of 1 to 4 above, wherein the lamination rate is 1 / sec or less. 6. A filter or filter unit in which the laminated filter medium according to any one of 1 to 5 above is pleated. 7. A method for producing a laminated filter medium according to any one of 1 to 6 above, comprising a heat fusing step of laminating a staple fiber web containing core-sheath staple fibers made of a polyolefin resin and a fiber sheet, and heat fusing the laminated filter medium by heating. 8. The manufacturing method described in 7 above, wherein in the heat fusion step, hot air having a temperature equal to or higher than the melting point of the sheath component of the core-sheath staple fibers is passed through the laminate obtained by stacking the staple fiber web and the fiber sheet, and the temperature of the hot air is set to a temperature at which the dimensional retention in the width direction of the fiber sheet before and after the passage is 94% or more. Effect of the Invention

[0010] According to the present invention, the mechanical properties of the laminated filter medium are optimized, the pleating processability is stabilized, and the dust retention amount can be increased while maintaining the breathability and collection efficiency of the filter or filter unit after pleating. Furthermore, by using the laminated filter medium of the present invention, a high-performance filter or filter unit can be provided. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram showing the configuration of a laminated filter medium of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a manufacturing facility for a laminated filter medium. [Diagram 3] 1 is a schematic diagram of an apparatus for measuring collection efficiency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. As shown in Fig. 1, the laminated filter medium 100 of the present invention is configured by laminating a short fiber layer 1 containing core-sheath short fibers made of polyolefin resin and a fiber sheet 2. The short fiber layer 1 functions to maintain the shape when the laminated filter medium 100 is pleated, and the fiber sheet 2 functions to capture fine dust. The short fiber layer 1 and the fiber sheet 2 are thermally fused together by heating to melt the sheath components of the core-sheath short fibers that make up the short fiber layer.

[0013] Pleated filters are generally obtained by pleating a laminated filter medium, and in general air conditioning filters, the pleats are assumed to be spaced 4.5 to 8.0 mm apart during filter processing, and to have a depth of 10 to 100 mm. In view of ease of pleating and fixing the pleats, the thickness of the laminated filter medium 100 is preferably 0.8 mm to 1.5 mm. The laminated filter medium needs a certain rigidity, or so-called bending resilience, for ease of processing and maintaining performance during use.

[0014] The laminated filter medium 100 of the present invention has a bending rebound characteristic of 56×10 -4 N or more 103×10 -4 N or less, preferably 59×10 -4 N or more 100×10 -4 By keeping the thickness below 56×10 N, it is possible to provide a filter with suitable pleating processability and shape retention, as well as a long life. -4 If the bending repulsion is less than 103×10 N, the stiffness of the filter medium is weak, and the pleats become uneven when pleated. In addition, when the pleated filter medium is fixed with molten bead resin, the bead resin gives in to the bending stress, and the fixed pleats become uneven. -4If the size is larger than N, it is not preferable to use the pleating method, known as the reciprocating method, in which two plates are alternately inserted above and below the filter medium and folded, because the ends of the plates cannot be folded neatly, resulting in irregular shaped apexes and uneven peak heights.

[0015] In addition, the laminated filter medium 100 has an air permeability of 33 cc / cm 2 / sec or more is preferable, and 35cc / cm 2 This range is suitable in terms of the balance between the airflow resistance and dust collection efficiency of the filter medium. 2 If the airflow rate is less than 1 / sec, the collection efficiency can be set high, but the airflow resistance of the filter medium increases, which is not preferable.

[0016] In order to satisfy the appropriate bending resilience characteristics and air permeability, the fiber sheet 2 needs to be made of an appropriate nonwoven fabric. As the sheet, wet-laid nonwoven fabric (paper), melt-blown nonwoven fabric, spunbond nonwoven fabric, etc. can be used, but it is preferable to use a polypropylene-based material that can be charged, and more preferably a melt-blown nonwoven fabric that can increase the polypropylene ratio and has appropriate air permeability as a filter material. In particular, it is preferable to use a nonwoven fabric with an air permeability of 39 cc / cm. 2 / sec or more is preferable when considering performance and productivity. If the air permeability is less than 36, the air permeability is poor, and although the efficiency of the sheet can be improved, it becomes difficult for the heated air to flow inside the sheet when bonding with air through, and wrinkles occur in the sheet, resulting in poor quality.

[0017] The staple fiber layer 1 has a weight per unit area of ​​65 to 95 g / m2 after bonding in order to satisfy the above-mentioned bending resilience characteristics. 2 , and even 70 to 90 g / m 2It is appropriate to set the weight to 95 g / m. The same weight may vary depending on the fineness and blending ratio of the core-sheath staple fibers used, and the higher the fineness of the material, the higher the bending resilience. However, 6.6T and 2.2T are generally the most readily available materials, and in this invention, 6.6T is used alone, or 6.6T and 2.2T are mixed. In particular, a blending ratio of 6.6T of 80% or more will provide an appropriate bending resilience at the above weight. When the weight is 95 g / m 2 If it is larger, the bending resilience will be high and the quality of the pleats will be poor.

[0018] Although it is possible to increase the ratio of fine fibers while increasing the basis weight, this is not realistic because it would tend to increase the airflow resistance relatively and the price. 2 If the thickness is less than 100 mm, appropriate bending resilience cannot be obtained, which leads to a decrease in pleat quality and a decrease in the amount of dust held when the pleated filter is used, and is therefore undesirable. In addition, as a method for suppressing the airflow resistance to a low level and increasing the dust collection efficiency in the present invention, a method is known in which the laminated filter medium is charged and used as a filter medium in a state in which the entire filter medium is charged with static electricity, and this method can also be applied to the present invention. In particular, by making the amount of oil attached to the short fiber layer 1 in the laminated filter medium 100 0.1% by weight or less, the short fiber layer 1 is also charged, and therefore the dust collection efficiency can be further increased.

[0019] Next, a manufacturing method for the laminated filter medium 100 will be described. The manufacturing equipment is shown in Fig. 2. The card web 3 is opened and carded, then dropped onto a conveyor by a cross layer 4 and laminated to form a short fiber web. A fiber sheet is pulled out from an unwinder 6 at the bottom of the machine so as to be laminated underneath the short fiber web, and lightly needle punched by a needle punch machine 5. The laminate is sandwiched between metal meshes 8 and continuously transported into an air-through oven 7, where it is heat fused (bonded) with hot air, and taken up by a take-up 9.

[0020] Here, for the short fiber web to be the short fiber layer 1, it is preferable to use core-sheath short fibers composed of polypropylene as the core and polyethylene as the sheath, and form the web by a known method, from the viewpoint of fusion properties and rationality of the process. When considering physical strength and air flow resistance, it is possible to use fibers of 2.2 to 22T for the core-sheath short fibers, but as described above, when considering the availability of raw cotton and appropriate bending resilience properties, it is more preferable to use fibers of 2.2 to 6.6T. Such polyolefin core-sheath short fibers are carded into a web by a known method. Other fibers to be mixed with the polyolefin core-sheath short fibers are selected according to the functions required as a filter. For example, when it is desired to impart antibacterial, high mold resistance, or flame retardancy, fibers to which known additives having such functions have been added may be mixed to the extent that electrostatic properties are not impaired. However, in the present invention, in order to set the bending resilience and air permeability in an appropriate range, core-sheath short fibers having a heat fusion portion, particularly polyolefin fibers containing various components, are preferably used as the fiber form. Furthermore, the oil adhering to the raw cotton is not necessary after the web is processed, and thermally deoiled fibers (manufactured by Ube Exsymo Co., Ltd.) that have the function of disappearing when heated are preferably used.

[0021] The short fiber web and the fiber sheet thus obtained are laminated and thermally bonded to obtain a laminated filter medium 100. A typical air-through oven 7 is used as a specific method of thermal bonding. First, the fiber sheet is placed on the heat-through oven for transport, and while being transported, the short fiber web is shaken off from above to form a laminate. At this time, it is important to lightly needle punch the laminate from above, that is, from the short fiber web side, in a laminated state before passing through the air-through oven. The needle punch conditions are preferably adjusted to a depth that does not damage the lower fiber sheet, and the needle density is not particularly limited as long as the fiber sheet and the short fiber web are temporarily in close contact with each other, but 40 / square inch or more is sufficient. The short fiber web and the fiber sheet are entangled by this needle punch, thereby reducing the transport failure that occurs when being transported to the air-through oven. Therefore, deep wrinkles in the fiber sheet part after bonding that occur during finishing are reduced, and a high-quality laminated filter medium 100 in good condition is manufactured. The pre-needle-punched laminate is sandwiched between metal meshes and passed through an air-through oven.

[0022] In order to obtain the necessary physical properties in the present invention, it is necessary to pass hot air having a temperature equal to or higher than the melting point of the sheath component of the thermally fusible fiber of the laminate being sandwiched and transported for a time that allows the heat to be sufficiently distributed in the thickness direction of the sheet. The transport time depends on the conditions of the equipment, but the temperature and the wind speed of the hot air are set for heating for 60 seconds to melt the sheath and bond the fibers together. The wind speed of the hot air is limited by the equipment, but it is carried out at 2.5 m / s or more, preferably 3 m / s or more. At a wind speed lower than this, the hot air does not pass sufficiently due to the breathability of the fiber sheet, and the finished thickness becomes large or the hot air circulation becomes uneven, causing wrinkles in the finished product. Furthermore, the temperature of the hot air is important. The temperature of the oven is set at a different measurement location depending on the equipment, and the temperature of the sheet actually tends to vary depending on the outside air, so it is difficult to absolutely specify the temperature. In addition, since it is actually difficult to accurately measure the surface temperature of the sandwiched sheet to the degree of 1°C, it is preferable to manage it by the dimensional retention rate of the width of the fiber sheet before and after it is placed in the oven at the finished time.

[0023] Specifically, in order to obtain the quality and appropriate physical properties of the nonwoven fabric, it is necessary that the width of the finished fiber sheet portion is 94% or more. If it is less than 94%, excessive heat is applied, so that the bending resilience may be set higher than the required range, and the finished nonwoven fabric may have shrinkage spots and become distorted, resulting in a decrease in quality. Note that a major feature of the present invention is that the laminated filter medium 100 having the specified physical properties and quality is manufactured in a single process, and a method of gradually adjusting the thickness from the commonly used bonding process using an air-through oven is not adopted. The finished laminated filter medium is rewound to the specified width. After being slit into the desired shape, the sheet is subjected to a charging process. The charging process may be carried out by a known method, for example, a corona charging method using a needle electrode.

[0024] The charged laminated filter medium 100 is folded in a zigzag pattern by a known method to form pleats, and is then framed with a method for maintaining a constant pleat interval, and used as a pleated filter or filter unit. The collection performance of a pleated filter depends on the characteristics of the filter medium, the filter medium area of ​​the pleated filter, and especially the pleat interval and pleat height, but is appropriately designed so that the linear passing velocity calculated for the filter medium area and the air volume of the air conditioner to be installed is 0.6 m / sec or less. The method for maintaining a constant pleat interval is not particularly limited as long as it is a method that can obtain a pleated filter, such as a method of sandwiching and fixing bead resin or spacers, a method of bonding and fixing the peaks of the pleats maintained at a constant interval with a rod-like material such as a bamboo stick, or a method of bonding the end faces of the filter temporarily held at a constant interval with a nonwoven fabric or cardboard. Thus, the scope of the present invention also includes pleated filters (pleated filters) and filter units. EXAMPLES

[0025] Next, the present invention will be specifically described using examples and comparative examples, but the present invention is not limited to only the examples.

[0026] The physical properties of the examples and comparative examples were measured by the following methods. Regarding the evaluation of the physical properties of the short fiber layer after heat and pressure bonding, the fiber sheet was peeled off from the laminated filter medium after heat and pressure bonding, and the following evaluations (1) and (2) were performed. (1) Weight (g / m 2 ) A square piece measuring 200 mm square was cut out, its weight was measured and divided by the dimensions. (2) Amount of oil applied A 2g sample was taken and soaked in 50cc of an extraction solution of ethanol / methanol: weight ratio 2 / 1 to extract the oil. The weights before and after extraction were measured to calculate the amount of extraction per unit weight (wt%).

[0027] The characteristics of the laminated filter medium were evaluated according to the following (3) to (7). (3) Breathability The breathability was measured in accordance with JIS L 1096 (2020) 8.26 Method A (Fragile method). (4) Weight (g / m 2 ) It was cut into a piece measuring 200 mm square, weighed, and divided by the dimensions. (5) Thickness (mm) The thickness was read at a load of 0.7 kPa. (6) Bending resilience The bending resilience was measured in accordance with JIS L 1096 (2020) 8.22.A Method (Gurley method). (7) Pressure loss, particle collection efficiency, quality factor (Qf) Using the measuring device shown in Fig. 3, a laminated filter material sample 18 was set in a duct 10, and air was allowed to flow at a linear velocity of 10 cm / sec. The flow rate of the air was adjusted by a flowmeter 15, a valve 16, and a blower 17 connected to the duct 10. The differential pressure between the upstream and downstream of the sample 18 was measured by a differential pressure gauge 13 to obtain the pressure loss. Furthermore, the air on the upstream and downstream sides was sampled, and the number of particles with a particle size of 0.3 to 0.5 µm was counted using a particle counter 14 connected to an upstream sampling pipe 11 and a particle counter 14 connected to a downstream sampling pipe 12. The particle collection efficiency (E) was calculated using the following formula 1, and the quality factor (Qf) was calculated using the following formula 2. Particle collection efficiency E (%) = {1-(number of particles downstream / number of particles upstream)} × 100 (Equation 1) Quality factor Qf(Pa -1 ) = -Ln(1-particle collection efficiency / 100) / pressure loss (Equation 2)

[0028] The characteristics of the filter unit were evaluated as described below in (7). (7) Pressure loss, average repair efficiency, and dust retention A charged laminated filter medium 605 mm wide x 20 m long was manufactured, pleated to a peak height of 58 mm, and bead resin was poured in at 25 mm intervals by a known method to form pleats with a peak pitch of 6.5 mm. The laminated filter medium was pleated into a filter unit and loaded into a 610 mm square aluminum frame, and the laminated filter medium was placed in a measuring device with the fiber sheet on the downstream side to measure pressure loss, JIS Class 11 average collection efficiency, and dust retention. A measuring device based on JIS B 9908 (2001) Type 2 was used as the measuring device. The air volume was 56 m 3 / min and the dust load was terminated at 294 Pa.

[0029] The charging method in the examples and comparative examples is as follows. (a) Charging device Earth side: A 2 mm thick silicone sheet was laid on a stainless steel cylindrical roll. Electrode side: Needle electrodes with a needle spacing of 10 mm were installed in a shape that matched the circumference of the cylindrical roll. Distance between electrode and ground: 10 mm from needle tip to silicone sheet (b) Charging method The heat-bonded sheet was transported between the electrodes with the short fiber layer side placed on the earth side of a cylindrical roll on which a silicone sheet was laid. Applied voltage: 20kV Charging time: 30 seconds

[0030] Examples are shown below. The manufacturing conditions in the examples vary depending on the individual manufacturing equipment, and are not intended to be limiting.

[0031] <Examples 1 to 3, Comparative Examples 1 to 3, 6, and 7> Composite filter media were manufactured by the method described below as filter media for filters set to each colorimetric grade in accordance with JIS B 9908:2001, Type 2. The staple fibers were polypropylene (core component) / polyethylene (sheath component) (polypropylene:polyethylene weight ratio was 1:1) (heat-resistant degreased fiber HR-LE manufactured by Ube Exsymo Co., Ltd.), and staple fibers with finenesses of 6.6T and 2.2T were made into webs by a carding machine, and were continuously laminated in a cross layer to make a staple fiber web. As a fiber sheet, a melt-blown polypropylene nonwoven fabric with the basis weight and breathability shown in Table 1 was prepared. The staple fiber web was laminated on the upper side and the fiber sheet was laminated on the lower side, and needle punching (needle density 40 / square inch) was performed from the upper side with the needle elongation adjusted to such an extent that holes would not be made in the fiber sheet, and the staple fiber web and the fiber sheet were entangled. In this state, the filter medium was passed through an air-through oven under the following conditions to obtain a laminated filter medium. Air-through oven temperature setting: The temperature at which the dimensional retention rate in the width direction of the fiber sheet before and after heat treatment is within a specified range. Transport time: 7 seconds Upper and lower mesh belt setting interval: 1mm Heated air speed: 3m / s

[0032] Regarding the obtained laminated filter medium, the physical properties of the fiber sheet, the short fiber layer, and the laminated filter medium were measured and are shown in Table 1.

[0033] <Comparative Example 4> A laminated filter medium was manufactured by the method described below as a filter medium for a filter with a colorimetric grade of 90% in accordance with JIS B 9908:2001, Type 2. Short fibers (6.6T20% 2.2T80% heat-resistant degreased fiber HR-LE manufactured by Ube Exsymo Co., Ltd.) composed of polypropylene (core component) / polyethylene (sheath component) (polypropylene:polyethylene weight ratio is 1:1) were made into a web by a carding machine, and the short fiber web was obtained by continuously laminating them in a cross layer. As a fiber sheet, a melt-blown polypropylene nonwoven fabric with the basis weight and breathability shown in Table 1 was prepared. The short fiber web was laminated on the upper side and the fiber sheet on the lower side, and needle punching (needle density 40 / square inch) was performed from the upper side with the needle elongation adjusted so that holes would not be made in the fiber sheet, and the short fiber web and the fiber sheet were entangled. In this state, it was passed through an air-through oven under the following conditions to obtain a laminated filter medium. Air-through oven temperature setting: The temperature at which the dimensional retention rate in the width direction of the fiber sheet before and after heat treatment is within a specified range. Transport time: 7 seconds Upper and lower mesh belt setting interval: 1mm Heated air speed: 3m / s

[0034] Furthermore, to adjust the thickness, the thickness was adjusted from 1.4 mm to 0.7 mm by passing it through a sheet laminator at a temperature of 140° C. Regarding the obtained laminated filter medium, the physical properties measured for the fiber sheet, the short fiber layer, and the laminated filter medium are shown in Table 1.

[0035] <Comparative Example 5> A laminated filter medium was manufactured by the method described below as a filter medium for a filter with a colorimetric grade of 90% in accordance with JIS B 9908:2001, Type 2. Short fibers (HR-CK manufactured by Ube Exsymo Co., Ltd.) consisting of polypropylene (core component) / polyethylene (sheath component) (polypropylene:polyethylene weight ratio is 1:1) were mixed and made into a web by a carding machine, and the short fiber web was made by continuously laminating them with a cross layer. As a fiber sheet, a melt-blown polypropylene nonwoven fabric with the basis weight and breathability shown in Table 1 was prepared. The short fiber web was laminated on the upper side and the fiber sheet on the lower side, and needle punching (needle density 40 / square inch) was performed from the upper side with the needle elongation adjusted so that the fiber sheet would not be punctured, and the short fiber web and the fiber sheet were entangled. In this state, it was passed through an air-through oven under the following conditions to obtain a laminated filter medium. Air-through oven temperature setting: The temperature at which the dimensional retention rate in the width direction of the fiber sheet before and after heat treatment is within a specified range. Transport time: 7 seconds Upper and lower mesh belt setting interval: 1mm Heated air speed: 3m / s

[0036] Regarding the obtained laminated filter medium, the physical properties of the fiber sheet, the short fiber layer, and the laminated filter medium were measured and are shown in Table 1.

[0037] [Table 1]

[0038] In Table 1, when compared at the same grade, it is clear that Examples 1 to 3 are high-performance laminated filter media suitable for pleating, compared to the Comparative Example. [Industrial Applicability]

[0039] According to the present invention, the mechanical properties of the laminated filter medium are optimized, the product quality and pleatability are stabilized, and the dust retention capacity of the pleated filter can be increased. In addition, when the oil content of the short fiber layer is 0.1% by weight or less, the short fiber layer can also be charged, and the dust collection efficiency can be increased without increasing the airflow resistance of the filter. This allows the airflow resistance of the filter to be reduced for a longer period of time, and the load on the equipment in which the filter is installed can be reduced. This is effective in saving energy for the equipment, and can contribute to resource saving with low environmental load.

Claims

1. In a laminated filter medium in which a short fiber layer containing core-sheath short fibers made of a polyolefin resin and a fiber sheet are laminated, The thickness is 0.8 mm or more and 1.5 mm or less, The short fiber layer and the fiber sheet are heat-sealed, Bending resilience is 56 x 10 -4 N or more 103×10 -4 N or less, and Breathability: 33cc / cm 2 / sec or more.

2. The weight of the short fiber layer is 65 g / m 2 95g / m or more 2 2. The laminated filter medium according to claim 1, wherein:

3. 2. The laminated filter medium according to claim 1, wherein the short fiber layer has an oil adhesion amount of 0.1% by weight or less and is electrically charged.

4. The core-sheath staple fiber has a polypropylene resin core and a polyethylene resin sheath, 2. The laminated filter medium according to claim 1, wherein the staple fiber layer contains two types of staple fibers having different finenesses as the core-sheath staple fibers, and the proportion of the staple fibers having the larger fineness in the staple fiber layer is 80% by weight or more.

5. The fiber sheet has an air permeability of 36 cc / cm 2 2. The laminated filter medium according to claim 1, characterized in that the filter medium has a flow rate of 100 s or less.

6. A filter or filter unit obtained by pleating the laminated filter medium according to any one of claims 1 to 5.

7. 2. The method for producing the laminated filter medium according to claim 1, comprising a heat fusing step of laminating a staple fiber web containing core-sheath staple fibers made of a polyolefin resin and a fiber sheet, and heat fusing the laminated filter medium by heating.

8. In the heat fusion step, Hot air having a melting point equal to or higher than the melting point of the sheath component of the core-sheath staple fibers is passed through a laminate obtained by laminating the staple fiber web and the fiber sheet, 8. The method according to claim 7, wherein the temperature of the hot air is set to a temperature at which the dimensional retention in the width direction of the fiber sheet before and after the passage of air is 94% or more.

Citation Information

Patent Citations

  • Filter medium

    JP1987083017A

  • Electret filter medium

    JP2012239995A

  • Electret filter material

    JP2014226629A